(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Importance of service industries was increased tremendously in the recent decade. Now the economy of our country largely depend on the service sector industry, which was earlier depended on the agriculture industry. Higher education is one of the significant service industry which helps to build the youth of the nation. In education especially higher education sector is the building block of our country. Delivering quality education or service especially in the higher education is the most challenging task. As the change is only the constant factor, rest others keep changing continuously. The expectation of the students is dynamic in nature studying in the college, which keeps on changing day after day. The various parameter of service quality is also dynamic. So their is a intense need to do the constant research on this particular domain. There are various models or conceptual framework already developed to analyze the service quality in the industries. The models are Gronroos Model, SERVQUAL Model, SERVPERF model, HEDPERF Model, HEISQUAL Model, Heirarchical Model etc. The present study will identify the various dimensions of service quality which is specific for the higher educational industry. Providing better service quality in higher educational institutions results in building the skilled manpower which are able to earn income through the Job, business or any other sources. The main elements involved in the service delivery mechanism are service provider and students. The new dimension identified is behavioural intention which measure the student satisfaction level in the higher educational institutions